2010
DOI: 10.1590/s1806-83242010000400007
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of planktonic cultures of Streptococcus mutans to photodynamic therapy with a light-emitting diode

Abstract: The objective of this study was to evaluate the effect of photodynamic therapy with erythrosine and rose bengal using a light-emitting diode (LED) on planktonic cultures of S. mutans. Ten S. mutans strains, including nine clinical strains and one reference strain (ATCC 35688), were used. Suspensions containing 10⁶ cells/mL were prepared for each strain and were tested under different experimental conditions: a) LED irradiation in the presence of rose bengal as a photosensitizer (RB+L+); b) LED irradiation in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0
9

Year Published

2012
2012
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 18 publications
2
30
0
9
Order By: Relevance
“…Several researchers have reported that PDT is capable of killing oral bacteria in planktonic cultures [21][22][23] and biofilm conditions [13,14]. If bacteria within dentine carious lesions can be eliminated by PDT, it might have positive consequences for dental health.…”
Section: Discussionmentioning
confidence: 99%
“…Several researchers have reported that PDT is capable of killing oral bacteria in planktonic cultures [21][22][23] and biofilm conditions [13,14]. If bacteria within dentine carious lesions can be eliminated by PDT, it might have positive consequences for dental health.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results have been shown in previous studies using different photosensitizers on oral bacteria. [38][39][40][41] One of the main observations made during the first tests to photoinactivate bacteria with conventional photosensitizers was the relative sensitivity of gram-positive strains to photodynamic inactivation. 24 This sensitivity was confirmed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…And the reduction rate in the isolated S. mutans appeared to be similar or slightly lower than the reference strain. Carolina et al 32) has verified the effect of photodynamic therapy with erythrosine using a LED on planktonic cultures of ten S. mutans strains, including nine clinical strains and one reference strain (ATCC 35688). The results showed that PDT with erythrosine exerted an antimicrobial effect on all S. mutans strains studied.…”
Section: ⅳ Discussionmentioning
confidence: 99%